Clinical Outcome and Quality of Life after Modular Reverse Total Shoulder Arthroplasty in Comparison with Joint‐Preserving Locking Plate Osteosynthesis in Aged Patients: A Retrospective Comparison Study - Carina Jaekel; Lisa Oezel; Franziska Leibnitz; Lena Marie Wilms; Joachim Windolf; Sebastian Viktor Gehrmann; Armin Olaf Scholz (Orthopaedic Surgery)
Objectives Proximal humeral fractures (PHFs) show a high incidence in aged patients. While nondisplaced fractures achieve good results by conservative treatment, surgical procedures are discussed controversially. Next to open reduction and internal fixation (ORIF), the primary use of reverse shoulder arthroplasty (RSA) has become increasingly important. The aim of this study was to investigate the clinical function, activities of daily living (ADL), as well as pain assessment in patients with PHFs, treated by ORIF or RSA. Methods A retrospective comparison study was assessed. From November 2011 to March 2016, 34 patients (17 matched pairs) that had undergone either ORIF or RSA of the proximal humerus, were included in this study. Pain was measured by numeric rating scale (NRS). ADL were obtained by Katz‐Index and SF‐12. Moreover, shoulder function was assessed using the Oxford Shoulder Score (OSS). The maximum range of motion (ROM) was also recorded. From November 2011 to March 2016, 34 patients (17 matched pairs) that had undergone either ORIF (Figure or RSA of the proximal humerus) were included in this study. For statistical analyses, Student's t‐test, Wilcoxon test, and Chi‐Quadrat test were used. Statistical significance was indicated with p < 0.05. Results Totally 34 patients with an average age of 76.6 years were included. Surgical treatment was performed on average 5.2 days after diagnosis, differing significantly between the two groups (RSA/ORIF: 6.9/3.5 days) The operation time of RSA (97 min) was significantly longer than for ORIF (78 min). Pain assessment, as well as the Katz‐Index and the SF‐12, showed no significant differences. Moreover, clinical shoulder function showed no significant discrepancies between the two surgical techniques. Conclusions Aged patients with PHFs treated with RSA display similar results regarding clinical function, ADL as well as pain perception compared with ORIF. However, revision surgery rate was lower in patients who underwent RSA. Thus, the surgical treatment of PHFs by RSA represents an excellent alternative, especially with regard to an aging patient population.